2017
DOI: 10.1093/nar/gkx704
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale detection of positive selection in nine primates predicts human-virus evolutionary conflicts

Abstract: Hotspots of rapid genome evolution hold clues about human adaptation. We present a comparative analysis of nine whole-genome sequenced primates to identify high-confidence targets of positive selection. We find strong statistical evidence for positive selection in 331 protein-coding genes (3%), pinpointing 934 adaptively evolving codons (0.014%). Our new procedure is stringent and reveals substantial artefacts (20% of initial predictions) that have inflated previous estimates. The final 331 positively selected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 89 publications
(145 reference statements)
9
74
1
Order By: Relevance
“…alleles are expressed in sperm. That hypothesis is consistent with recent evidence for genomewide positive selection on primate genes (including C4BPA) that encode proteins involved in innate immunity (van der Lee et al 2017). In that study, positive selection for nonsynonymous substitutions among primate species was correlated with the accumulation of nonsynonymous polymorphisms within the human lineage in the same genes (including polymorphisms in C4BPA), and was interpreted as evidence of ongoing selection among humans driven by viruses and other pathogens.…”
Section: Significance Of Coevolution Among Human Fertilization Genessupporting
confidence: 90%
“…alleles are expressed in sperm. That hypothesis is consistent with recent evidence for genomewide positive selection on primate genes (including C4BPA) that encode proteins involved in innate immunity (van der Lee et al 2017). In that study, positive selection for nonsynonymous substitutions among primate species was correlated with the accumulation of nonsynonymous polymorphisms within the human lineage in the same genes (including polymorphisms in C4BPA), and was interpreted as evidence of ongoing selection among humans driven by viruses and other pathogens.…”
Section: Significance Of Coevolution Among Human Fertilization Genessupporting
confidence: 90%
“…The latter include components of the innate, cellular and systemic host immune response that directly interact with viruses to limit or clear infections. Genes associated with host antiviral mechanisms frequently show elevated evolutionary rates and evidence for positive selection once engaged in an intricate arms race with their virus targets that aim to counter their antiviral functions [92][93][94][95] . Accelerated niche-associated evolution in such genes may indeed reproduce the power law relationships between observation period and virus substitution rates ( fig.…”
Section: Niche Evolutionmentioning
confidence: 99%
“…PGR was ranked 8 th in a genome-wide scan for positive selection in human-chimp-mouse gene trios [32] and 29 th among genes with the strongest statistical evidence of positive selection in a pair-wise genome-wide scan for positively selected genes in human and chimpanzee genomes [33]. In contrast, evidence of positive selection on PGR was not detected in the human lineage in analyses of human-chimp-macaque gene trios [34], human-chimp-mouserat-dog orthologs [35], a dataset including seven primates [36], or a dataset including nine primates [37]. A study of human-chimp-macaque-mouse-rat-dog orthologs found evidence for a positively selected class of sites in the human lineage (4.45%, d N /d S = 3.15), but the results were not statistically significant (LRT P = 0.46) [38].…”
Section: Introductionmentioning
confidence: 97%